2000
DOI: 10.1007/s004060070017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, quality of life and psychosocial function in obsessive-compulsive disorder and subclinical obsessive-compulsive disorder in northern Germany

Abstract: Due to different epidemiological characteristics subclinical OCD might represent a syndrome distinct from OCD which is also associated with significant impairments in personal and interpersonal functions and in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
81
3
7

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 21 publications
11
81
3
7
Order By: Relevance
“…Our findings suggest that OCS without further sub-clinical features is indeed clinically meaningful, both in its own right and in the extremely common presentation with comorbid conditions. The 12-month prevalence of OCD found in this study (0.7%) corresponds to previous studies conducted on the general population, with ranges from 0.3 to 3.0% [2,7,9,23,31,37,50,53,57]. Twelve-month prevalence rates of 0.6 to 4.9% for subthreshold OCD that fulfill some but not all the required DSM-IV criteria of threshold OCD (4.5%) is likewise consistent with previous studies [3,9,22,53].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Our findings suggest that OCS without further sub-clinical features is indeed clinically meaningful, both in its own right and in the extremely common presentation with comorbid conditions. The 12-month prevalence of OCD found in this study (0.7%) corresponds to previous studies conducted on the general population, with ranges from 0.3 to 3.0% [2,7,9,23,31,37,50,53,57]. Twelve-month prevalence rates of 0.6 to 4.9% for subthreshold OCD that fulfill some but not all the required DSM-IV criteria of threshold OCD (4.5%) is likewise consistent with previous studies [3,9,22,53].…”
Section: Discussionsupporting
confidence: 55%
“…By demonstrating the impact of OCS, our results added important evidence to previous research on subthreshold OCD. It has been argued that OCD should be defined using less restrictive criteria because subthreshold OCD might better describe the clinical reality of individuals who suffer from this symptomatology [23,52]. Our findings suggest that OCS without further sub-clinical features is indeed clinically meaningful, both in its own right and in the extremely common presentation with comorbid conditions.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Most rates were found to be higher for women than for men but several studies demonstrated higher rates for men, compared with women (32,34,38). For studies reporting higher female rates, most rates were 1.1 to 1.8 times higher for women than for men, while one study found a female rate that was 14.8 times that of the male rate (77). With regard to GAD, the 1-year and lifetime rates were generally found to be 1.5 to 2 times higher for women, compared with men.…”
Section: Sex-specific Prevalencementioning
confidence: 97%
“…Das Aufsuchen professioneller Hilfe als Ausdruck einer bereits so definierten "Krankheit" war die Ausnahme, verzögerte Inanspruchnahme therapeutischer Hilfe aber eher die Regel. Die Tatsache, dass Patienten mit Zwangserkrankungen im Mittel 7-10 Jahre nach dem Auftreten von Zwangssymptomen erstmals therapeutische Hilfe in Anspruch nehmen [12] und zu diesem Zeitpunkt oft schon ein hoher Grad an Chronifizierung [13,14] Der Forschungsbedarf an Studien zur frühen Identifikation von Zwangserkrankungen ist aufgrund mangelnder "Objektivierbarkeit" des tatsächlichen Krankheitsausbruches nicht gedeckt. Die Entwicklung eines Symptominventars, das neben diesen retrospektiv erfassten frühen Auffälligkeiten, ergänzende Informationen der Angehörigen und "objektive" Kriterien der Professionellen enthält, ist notwendig.…”
unclassified